Fitrah-Based Parenting Education Training to Improve Parents' Knowledge of Nurturing Children’s Fitrah in the Digital Age - Sulaimawan, Deddy; Nurhayati, Sri (Kawanua International Journal of Multicultural Studies, 2023)
The objective of this study is to determine the level of effectiveness of Fitrah-based parenting education in improving parents' knowledge of nurturing children’s fitrah- based on Qur'anic values. The study uses the quasi-experimental method and a pre and post-test design for a single group. In February of 2023, thirty parents of children who attended Nurul Islam Al Husna Community Learning Center participated in a study conducted in Cimahi City. The treatment consisted of Fitrah-based parenting education, which addressed the importance of fitrah-based parenting in the digital era, the impact of technology on children's development, as well as parenting strategies on how to nurture children’s fitrah. Wilcoxon signed rank test was selected as the method for statistical analysis. The result revealed that there are significant differences between before and after training on the parents’ knowledge of nurturing children’s fitrah.